Postpartum pheochromocytoma-induced takotsubo syndrome. Issue 3 (19th March 2021) - Itagane, Masaki; Nakazato, Jun; Kinjo, Mitsuyo
Abstract : A postpartum patient with acute-onset dyspnoea and hypotention, associated with reduced left ventricular function requiring intensive blood pressure control, was initially misdiagnosed as having peripartum cardiomyopathy. Her clinical symptoms rapidly resolved. Echocardiography revealed reversible left ventricular dysfunction with apical ballooning and coronary angiography was normal. Based on these findings, we diagnosed takotsubo syndrome. Over the next two months, the patient experienced repeated bouts of elevated sympathetic activity. On workup, we found an adrenal mass and elevated urine metanephrines. After adrenalectomy, histology confirmed pheochromocytoma. Our patient had the rare diagnosis of postpartum pheochromocytoma-induced takotsubo syndrome.